Recent advancement in waste water management : implication and biological solutions - Ferreira, Luiz Fernando Romanholo; Kumar, Ajay; Bilal, Muhammad (Advances in chemical pollution, environmental management and protection, 2023)
APMP Volume Nine: Recent Advancement In Waste Water Management: Implication and Biological Solutions highlights new advances in the field, with this new volume presenting interesting chapters on antibiotics and hormone residues in wastewater: Occurrence, risks, and its biological, physical and chemical treatments, Occurrence of pesticides in wastewater: Bioremediation approach for environmental safety and its toxicity, Removal of pharmaceutical compounds from water, Biological solutions for the removal of microplastics from water, Impact of wastewater irrigation on soil attributes, Factors influencing the wastewater treatment process from agro-industrial effluents through microalgae and advanced oxidative processes, and more. Other sections cover Contamination of soil and food chain through wastewater application and Advanced biomaterials for the removal of pesticides from water.